How much of federalism in the European Union - František Turnovec (Charles University in Prague, Institute of Economic Studies (IES), 2009)
The European Union (EU) is not de jure a federation, but after 50 years of institutional evolution it possesses attributes of a federal state. One can conclude that EU is something between federation and intergovernmental organization. If we measure something between by interval [0, 1], where 0 means fully intergovernmental organization and 1 means de facto federation, the questions are: What is the location of recent EU on this interval? What tendency of development of this location can be observed in time? In this paper we propose such a measure based on game-theoretical model of European Union decision making system.
Keywords: C71; D72; H77; 330; co-decision procedure; committee system; consultation procedure; European Union decision making; federation; intergovernmental organization; qualified majority; power indices; simple voting committee; Föderalismus; Politische Entscheidung; Machtindex; Spieltheorie; EU-Staaten